Much ado about nothing? Do domestic firms really benefit from foreign direct investment? - Holger Görg; David Greenaway (Institute for the Study of Labor (IZA), 2003)
Governments the world over offer significant inducements to attract inward investment, motivated by the expectation of spillover benefits to augment the primary benefits of a boost to national income from new investment. This paper begins by reviewing possible sources of FDI induced spillovers. It then provides a comprehensive evaluation of the empirical evidence on productivity, wages and exports spillovers in developing, developed and transitional economies. Although theory can identify a range of possible spillover channels, robust empirical support for positive spillovers is, at best, mixed. The reasons for this are explored and the paper concludes with a review of policy aspects.
Keywords: F21; F23; 330; foreign direct investment; multinationals; spillovers; productivity; wages; exports; Direktinvestition; Spillover-Effekt; Produktivität; Lohn; Technologietransfer; Theorie; Welt